Islamic Thought and Internationalization of Human Rights - Reza Ahmad Zahid (Institut Agama Islam Tribakti (IAIT) Kediri, 2019)
This article aims to answer how Islamic thought deals with issues of internationalization. Where in general religions agree that human rights are rights owned by each individual solely because of his dignity as a human being, not the construction of society regarding individual rights. While on the other hand, some experts state that human rights are normative elements that are inherent in human individuals because there are laws whose application differs according to space and time. Between Islam and human rights has a relationship that lies in the universality of Islamic teachings. the concept of human rights has been outlined in the basic principles of Islamic law originating from the texts of the Koran, the Sunnah of the Prophet and friends, as well as the construction of scholars' thoughts. Human rights should be understood and accepted as a universal human treasure whose normative and philosophical foundations can be traced and found in various systems of values ?and traditions. Such global ethics cannot be formulated without religious contributions.